Fraud Hexagon From East Java Education Department - Susilawati Agraeni, Leny; Jumri; Kadafi, Muhammad (Yayasan Pendidikan Belajar Berdikari, 2023)
The number of corruption cases in Indonesia is rising; the ministry of education sees an annual increase in corruption cases, and the country is among the top five areas in the world for the number of corruption cases. The majority of corruption cases in Indonesia are committed by civil servants. Both public confidence in the government and government performance may suffer as a result. Based on the opinions of Education Service personnel, this study attempts to examine the effects of Pressure, Collusion, Capability, Opportunity, Rationalization, and Ego on Corruption. There were 253 workers at one of the East Java Regional Education Services that made up the study's population. A total of 82 respondents were included in the convenience sampling, which was conducted. Using IBM SPSS Statistics 25 software, multiple linear regression analysis is used in this study to evaluate hypotheses through the distribution of questionnaires and primary data collected through quantitative research. According to this study, ego has a strong detrimental impact on corruption while rationalization has a favorable and large impact. In the meanwhile, corruption is unaffected by pressure, collusion, capability, and opportunity. Because Fraud Hexagon is still relatively new, there aren't many comparable references in this research, which is one of its drawbacks. Another is that the direct distribution of questionnaires takes a long time. The distribution was restricted to one government agency, which further confined the research area and the samples used.